Bioactive glass-based materials with hierarchical porosity for medical applications: Review of recent advances. (15th September 2016) - Baino, Francesco; Fiorilli, Sonia; Vitale-Brovarone, Chiara
Graphical abstract: Abstract: Bioactive glasses have been traditionally used in the clinical practice to fill and restore osseous defects due to their unique ability to bond to host bone and stimulate new bone growth. In the last decade, a new set of bioactive glasses characterized by a highly ordered mesoporous texture has been developed and studied as a smart platform for the controlled release of biomolecules, in situ therapy and regenerative applications. This review points out the great potential carried by hierarchical bioactive glass scaffolds that exhibit pore scales from the meso- to the macro-range, and their impact in the broad field of tissue engineering, including the emerging applications in contact with soft tissues and diagnostics. Recent advances in the preparation methods of these multiscale constructs (e.g. mono- or multi-phase scaffolds, fibrous meshes, coated systems, porous nanospheres, and composites) are examined, along with their strengths and weaknesses. A bright future is expected for hierarchical systems based on biocompatible mesoporous materials as they can provide a unique set of functionalities, including enhanced bioactivity, local release of ions and drugs to elicit specific therapeutic effects (improved osteogenesis and angiogenesis, antibacterial properties), and implant/drug tracking, which were unthinkable when research on bioactive glasses began. Statement of Significance: The advent of mesoporous bioactive glasses led to the birth of a new class of multifunctional biomaterials that have been proposed as smart platforms for local drug release and bone regeneration. Furthermore, mesoporous materials have been recently employed in the development of hierarchical macro-mesoporous scaffolds, composites and implantable systems. This reviews summarizes the latest applications of these multiscale biomaterials in tissue engineering, including the emerging applications in contact with soft tissues and diagnostics. The preparation methods, current uses and potential of these constructs and systems are examined and critically discussed to provide a useful, up-to-date contribution to the scientists working in the field.